An overview of approaches to the study of public policy - Anyebe, Adam A. (Penerbit Universiti Kebangsaan Malaysia, 2018)
Political and social scientists have developed many theories, models and approaches for analysing policy-making. The theoretical approaches include elite theory, group theory, political systems theory and institutionalism, policy output analysis, incremental theory and rational-choice theory which are primarily concerned with public policy-making as a process. This paper therefore, attempts to examine each theory, pointing out its strengths and limitations. The study relied heavily on secondary sources for data collection. The paper reveals that one cannot authoritatively see which of these theoretical approaches is the best or the most satisfactory as each approach focuses on different aspects of policy-making, and this seems more useful for understanding some situations or events than others. It seems wise not to be bound too dogmatically to one approach. A good rule for the policy maker is to be eclectic and flexible, and to draw from theories that seem most useful for the satisfactory and fair-minded description and explanation of policies. The objective explanation of political behaviour rather than the validation of one’s preferred theoretical approach should be the goal of political inquiry. Each of the theories discussed, if drawn upon skilfully and selectively, can contribute to a better understanding of policy-making.